Semiconductor laser element

The semiconductor laser device addresses absorption loss in nitride semiconductor laser devices by structuring the p-side semiconductor layer with an undoped compositionally graded layer and a thinner p-type impurity-containing portion, enhancing efficiency and reducing drive voltage.

JP7617458B2Active Publication Date: 2025-01-20NICHIA CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023120613
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-01-17
Filing Date
2023-07-25
Publication Date
2025-01-20
Estimated Expiration
2039-07-31

AI Technical Summary

Technical Problem

The absorption loss in the p-type impurity-containing layer of nitride semiconductor laser devices increases with light intensity, leading to decreased efficiency, particularly in devices operating in the green wavelength band, due to deep levels and light absorption caused by p-type impurities like Mg.

Method used

The semiconductor laser device is designed with a p-side semiconductor layer comprising an undoped first portion, an electron barrier layer, and a thinner p-type impurity-containing second portion, where the first portion has a compositionally graded layer with increasing band gap energy, and the ridge's lower end is located in the undoped intermediate layer, reducing light absorption and improving efficiency.

Benefits of technology

This configuration reduces absorption loss and improves efficiency by minimizing light absorption in the p-type impurity-containing layers, stabilizing the horizontal transverse mode, and reducing drive voltage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617458000001
    Figure 0007617458000001
  • Figure 0007617458000002
    Figure 0007617458000002
  • Figure 0007617458000003
    Figure 0007617458000003
Patent Text Reader

Abstract

To provide a semiconductor laser element capable of reducing an absorption loss and of improving efficiency.SOLUTION: A semiconductor laser element has an n-side semiconductor layer, an active layer, and a p-side semiconductor layer upward in this order, which are composed of nitride semiconductors respectively, and is provided with a ridge projecting upward in the p-side semiconductor layer. The p-side semiconductor layer has: a first part which is undoped, is arranged in contact with an upper surface of the active layer, and has one or more semiconductor layers; an electron barrier layer which is arranged in contact with an upper surface of the first part, is greater in band-gap energy than the first part and contains p-type impurity; and a second part which is arranged in contact with an upper surface of the electron barrier layer and has one or more p-type semiconductor layers containing p-type impurity. The first part has a p-side composition inclined layer which is undoped and becomes greater in band-gap energy as it goes up and a p-side intermediate layer which is arranged above the p-side composition inclined layer and undoped. A lower end of the ridge is positioned in the p-side intermediate layer.SELECTED DRAWING: Figure 2A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a semiconductor laser device. [Background technology]

[0002] Nowadays, semiconductor laser elements having nitride semiconductors (hereinafter also referred to as "nitride semiconductor laser elements") are capable of emitting light ranging from the ultraviolet region to green, and are used in a wide range of applications, including as light sources for optical discs. Known as such semiconductor laser elements are those having an n-side cladding layer, an n-side optical guide layer, an active layer, a p-side optical guide layer, and a p-side cladding layer in this order on a substrate (e.g., Patent Documents 1, 2, and 3). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2003-273473 A [Patent Document 2] JP 2014-131019 A [Patent Document 3] International Publication No. 2017 / 017928 Summary of the Invention [Problem to be solved by the invention]

[0004] The p-side semiconductor layer of a nitride semiconductor laser element is doped with p-type impurities such as Mg, but the p-type impurities create deep levels and cause optical absorption. Therefore, the higher the optical intensity in the p-type impurity-containing layer, the greater the absorption loss, and the lower the efficiency, such as the slope efficiency. Therefore, this disclosure proposes a semiconductor laser element that can reduce the absorption loss and improve the efficiency. [Means for solving the problem]

[0005] A first aspect of a semiconductor laser element according to the present disclosure is a semiconductor laser element including, in order from top to bottom, an n-side semiconductor layer, an active layer, and a p-side semiconductor layer, each of which is made of a nitride semiconductor, and in which a ridge protruding upward is provided in the p-side semiconductor layer, The p-side semiconductor layer is a first portion that is disposed in contact with an upper surface of the active layer, has one or more semiconductor layers, and is undoped; an electron barrier layer that is disposed in contact with an upper surface of the first portion, has a band gap energy larger than that of the first portion, and contains a p-type impurity; a second portion disposed in contact with an upper surface of the electron barrier layer and having one or more p-type semiconductor layers containing p-type impurities; The first portion is The band gap energy increases toward the top, and the p-side compositionally graded layer is undoped. The semiconductor laser element has an undoped p-side intermediate layer disposed above the p-side compositionally graded layer, and a lower end of the ridge is located in the p-side intermediate layer.

[0006] A second aspect of the semiconductor laser element according to the present disclosure is a semiconductor laser element including, in order from top to bottom, an n-side semiconductor layer, an active layer, and a p-side semiconductor layer, each of which is made of a nitride semiconductor, and in which a ridge protruding upward is provided in the p-side semiconductor layer, The p-side semiconductor layer is a first portion that is disposed in contact with an upper surface of the active layer, has one or more semiconductor layers, and is undoped; an electron barrier layer that is disposed in contact with an upper surface of the first portion, has a band gap energy larger than that of the first portion, and contains a p-type impurity; a second portion disposed in contact with an upper surface of the electron barrier layer and having one or more p-type semiconductor layers containing p-type impurities; The thickness of the second portion is smaller than the thickness of the first portion, The lower end of the ridge is a semiconductor laser element located in the first portion.

[0007] A first aspect of a method for manufacturing a semiconductor laser device according to the present disclosure includes: forming an n-side semiconductor layer on a substrate; forming an active layer on the n-side semiconductor layer; forming an undoped first portion having one or more semiconductor layers on an upper surface of the active layer; forming an electron barrier layer on a top surface of the first portion by doping with a p-type impurity, the electron barrier layer having a band gap energy larger than a band gap energy of the first portion; forming a second portion having one or more p-type semiconductor layers formed by doping a p-type impurity on an upper surface of the electron barrier layer; forming an upwardly protruding ridge by removing a part of the p-side semiconductor layer including the first portion, the electron barrier layer, and the second portion; The step of forming the first portion undoped includes: forming an undoped p-side compositionally graded layer having a band gap energy increasing upward; forming an undoped p-side intermediate layer above the p-side composition graded layer, wherein in the ridge forming step, a portion of the p-side semiconductor layer is removed so that a lower end of the ridge is located in the p-side intermediate layer. A second aspect of the method for manufacturing a semiconductor laser device according to the present disclosure includes: forming an n-side semiconductor layer on a substrate; forming an active layer on the n-side semiconductor layer; forming an undoped first portion having one or more semiconductor layers on an upper surface of the active layer; forming an electron barrier layer on a top surface of the first portion by doping with a p-type impurity, the electron barrier layer having a band gap energy larger than a band gap energy of the first portion; forming a second portion having one or more p-type semiconductor layers formed by doping a p-type impurity on an upper surface of the electron barrier layer; forming an upwardly protruding ridge by removing a part of the p-side semiconductor layer including the first portion, the electron barrier layer, and the second portion; In the step of forming the second portion, the second portion is formed to have a thickness smaller than a thickness of the first portion; In the step of forming the ridge, a part of the p-side semiconductor layer is removed so that a lower end of the ridge is located at the first portion. Effect of the Invention

[0008] With such a semiconductor laser device, the absorption loss can be reduced and the efficiency can be improved. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view of a semiconductor laser device according to one embodiment of the present invention. [Figure 2A] FIG. 2A is a diagram illustrating an example of a layer structure of a p-side semiconductor layer of the semiconductor laser device of FIG. [Figure 2B] FIG. 2B is a diagram illustrating another example of the layer structure of the p-side semiconductor layer of the semiconductor laser element of FIG. [Figure 2C] FIG. 2C is a diagram illustrating another example of the layer structure of the p-side semiconductor layer of the semiconductor laser element of FIG. [Figure 2D] FIG. 2D is a diagram illustrating another example of the layer structure of the p-side semiconductor layer of the semiconductor laser element of FIG. [Figure 3A] FIG. 3A is a diagram illustrating an example of the relationship between the band gap energies of the top layer of the first portion, the electron barrier layer, and the bottom layer of the second portion. [Figure 3B] FIG. 3B is a diagram illustrating another example of the relationship in band gap energy between the uppermost layer of the first portion, the electron barrier layer, and the lowermost layer of the second portion. [Figure 3C] FIG. 3C is a diagram illustrating another example of the relationship in band gap energy between the top layer of the first portion, the electron barrier layer, and the bottom layer of the second portion. [Figure 4] FIG. 4 is a diagram illustrating an example of a layer structure of the n-side semiconductor layer of the semiconductor laser element of FIG. [Diagram 5] FIG. 5 is a partially enlarged view of the p-side compositionally graded layer and its vicinity of the semiconductor laser device of FIG. [Figure 6A] FIG. 6A is a flowchart showing a method for manufacturing a semiconductor laser device according to one embodiment of the present invention. [Figure 6B] FIG. 6B is a flowchart showing an example of step S103. [Figure 7] FIG. 7 is a graph showing the relationship between the thickness of the first portion and the proportion of leaked light to the second portion in calculation examples 1 to 5. [Figure 8] FIG. 8 is a graph showing the IL characteristics of the semiconductor laser devices of Comparative Examples 1 to 4. In FIG. [Figure 9A] FIG. 9A is a graph showing the IL characteristics of the semiconductor laser devices of Examples 1 to 3. [Figure 9B] FIG. 9B is a graph showing the IV characteristics of the semiconductor laser devices of Examples 1 to 3. [Figure 10A] FIG. 10A is a graph showing the IL characteristics of the semiconductor laser devices of Examples 3 to 5. [Figure 10B] FIG. 10B is a graph showing the IV characteristics of the semiconductor laser devices of Examples 3 to 5. [Figure 11A] FIG. 11A is a graph showing the IL characteristics of the semiconductor laser devices of Examples 3 and 6. [Figure 11B] FIG. 11B is a graph showing the IV characteristics of the semiconductor laser devices of Examples 3 and 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. However, the embodiment shown below is merely an example of a method for realizing the technical idea of ​​the present invention, and the present invention is not limited to the following embodiment. Furthermore, in the following description, the same names and symbols indicate the same or similar components, and detailed description will be omitted as appropriate.

[0011] FIG. 1 is a schematic cross-sectional view of the semiconductor laser device 100 according to this embodiment, showing a cross section in a direction perpendicular to the resonator direction of the semiconductor laser device 100. FIG. 2A, FIG. 2B, FIG. 2C, and FIG. 2D are all diagrams showing schematic examples of the layer structure of the p-side semiconductor layer 4, each showing a different example. Also, FIG. 2A to FIG. 2D are diagrams showing schematic relationships in band gap energy between a part of the active layer 3 of the semiconductor laser device 100 and each layer of the p-side semiconductor layer 4. In FIG. 2A to FIG. 2D, the position of the bottom surface of the ridge 4a is shown by a dashed line. The bottom surface of the ridge 4a refers to a surface connecting the lowest sides of both sides of the ridge 4a. FIG. 4 is a diagram showing schematic examples of the layer structure of the n-side semiconductor layer 2.

[0012] 1, the semiconductor laser element 100 has an n-side semiconductor layer 2, an active layer 3, and a p-side semiconductor layer 4, each made of a nitride semiconductor, arranged in this order from top to bottom. The p-side semiconductor layer 4 is provided with a ridge 4a that protrudes upward. In this specification, the direction from the n-side semiconductor layer 2 toward the p-side semiconductor layer 4 is referred to as "up" or "upward," and the opposite direction is referred to as "down" or "downward."

[0013] The p-side semiconductor layer 4 has a first portion 41, an electron barrier layer 42, and a second portion 43. The first portion 41 is disposed in contact with the upper surface of the active layer 3, and has one or more semiconductor layers. The first portion 41 is undoped. The electron barrier layer 42 is disposed in contact with the upper surface of the first portion 41. The electron barrier layer 42 has a band gap energy larger than that of the first portion 41, and contains a p-type impurity. The second portion 43 is disposed in contact with the upper surface of the electron barrier layer. The second portion 43 has one or more p-type semiconductor layers containing a p-type impurity. The lower end of the ridge 4a is located in the first portion 41. That is, the ridge 4a is composed of a part of the first portion 41, the electron barrier layer 42, and the second portion 43. In this specification, undoped means that the doping is not intentionally performed. A concentration that does not exceed the detection limit in the analysis results of secondary ion mass spectrometry (SIMS) or the like may be called undoped. Alternatively, an impurity concentration of 1×10 17 / cm 3 For example, the first portion 41 may be said to be undoped when the concentrations of p-type impurities and n-type impurities are below the detection limit. However, since the first portion 41 is in contact with the electron barrier layer 42 having a high concentration of p-type impurities, p-type impurities may be detected in the analysis results even if the first portion 41 is formed without being intentionally doped with p-type impurities. In this case, the concentration of p-type impurities detected is 1×10 18 / cm 3 It is preferable that the thickness is less than 100 nm. When the first portion 41 and the like are formed undoped, unintended impurities such as H and C may be contained, but this case can also be called undoped. In this specification, the film thickness or thickness of a certain layer or part refers to the shortest distance from the bottom surface to the top surface of the layer or part. When the bottom surface and / or the top surface have partial concave and / or convex portions such as V-pits, the shortest distance between flat portions of the bottom surface and / or the top surface that do not have such concave and / or convex portions may be the film thickness or thickness of the layer or part.

[0014] The semiconductor laser device 100 has the following structures (1) to (3). (1) The first portion 41 has an undoped p-side compositionally graded layer 411 whose band gap energy increases toward the top, and an undoped p-side intermediate layer 412 disposed above the p-side compositionally graded layer 411. The lower end of the ridge is located in the p-side intermediate layer 412. (2) The second portion 43 is thinner than the first portion 41, and the lower end of the ridge 4a is located in the first portion 41. (3) The first portion 41 is 400 nm or more thick, and the lower end of the ridge 4a is located in the first portion 41. The semiconductor laser device 100 may have only one of the structures (1) to (3), or may have two or more of them at the same time.

[0015] First, (1) will be described. As shown in FIG. 2A, the p-side composition graded layer 411 is a layer whose band gap energy increases toward the top. With such a configuration, the light confinement in the active layer 3 can be strengthened. The p-side intermediate layer 412 is a layer different from the p-side composition graded layer 411. By providing not only the p-side composition graded layer 411 but also the p-side intermediate layer 412, the first portion 41 can be made relatively thick. This makes it possible to move the peak of the light intensity away from the electron barrier layer 42 and the second portion 43, which are portions containing p-type impurities. With these configurations, the light intensity in the second portion 43 can be reduced, and the light absorption loss can be reduced. Therefore, the efficiency of the semiconductor laser element 100 can be improved. The efficiency of the semiconductor laser element 100 can be exemplified by the slope efficiency, which is the slope in a characteristic graph of the current and the light output at a current value equal to or higher than the threshold current.

[0016] The lower end of the ridge 4a is located in the p-side intermediate layer 412, deeper than the electron barrier layer 42. This allows the distance between the lower end of the ridge 4a and the active layer 3 to be short, even if the first portion 41, which is a relatively thick film, is provided. Therefore, the lateral light confinement can be strengthened compared to the case where the lower end of the ridge 4a is located above the first portion 41. If the lateral light confinement is weak, the horizontal lateral mode of the semiconductor laser device 100 becomes unstable, and a kink may occur in the IL characteristic that indicates the relationship between the current and the optical output. By forming the ridge 4a so that its lower end is located in the p-side intermediate layer 412, the lateral light confinement can be strengthened and the horizontal lateral mode can be stabilized, thereby reducing the probability of kink occurrence in the IL characteristic. On the other hand, since there is a possibility that electrical leakage may occur at the lower end of the ridge 4a due to etching damage or the like during the formation of the ridge 4a, it is preferable that the lower end of the ridge 4a is not too close to the active layer 3. For this reason, it is preferable that the lower end of the ridge 4a is located in the p-side intermediate layer 412, not in the p-side compositionally graded layer 411.

[0017] Next, (2) will be described. Since the first portion 41 is a relatively thick film, the peak of the light intensity can be moved away from the p-type impurity-containing layer, as in (1), and the loss due to free carrier absorption in the p-type impurity-containing layer can be reduced. Therefore, the efficiency of the semiconductor laser element 100, such as the slope efficiency, can be improved. In addition, since the second portion 43 is thin, the driving voltage of the semiconductor laser element 100 can be reduced, and the efficiency can be improved. The reason why the voltage is reduced by reducing the film thickness of the portion containing p-type impurities is that in nitride semiconductors, p-type impurities such as Mg have a lower activation rate than n-type impurities such as Si, and the p-type impurity-containing layer has a relatively high resistance. Although the first portion 41 is undoped, it is located between the electron barrier layer 42 and the active layer 3, and therefore tends to exhibit n-type conductivity rather than complete insulation due to factors such as electron overflow. From these points, it is considered that the driving voltage can be reduced by reducing the thickness of the second portion 43 containing the p-type impurity, which has a relatively high resistance, and the effect of suppressing the increase in the driving voltage caused by increasing the thickness of the undoped first portion 41 can be obtained. This effect was confirmed in Experimental Result 2 for Examples 1 to 3 described below. As in (1), since the first portion 41 is a relatively thick film, it is preferable to provide the lower end of the ridge 4a in the first portion 41, which can enhance the lateral light confinement.

[0018] Next, we will discuss (3). The first portion 41 is relatively thick, at 400 nm or more, which makes it possible to reduce losses in the p-type impurity-containing layer and improve efficiency, as in (1) and (2). Furthermore, by locating the bottom end of the ridge 4a on the first portion 41, it is possible to enhance lateral light confinement, as in (1) and (2).

[0019] A simulation of the equivalent refractive index was performed by assuming a plurality of patterns for the configuration of the first portion 41. In this simulation, the refractive index of each layer was calculated based on the composition ratio of the nitride semiconductor constituting the layer using the formula described in MJBergmann, et. Al., JOURNAL OF APPLIED PHYSICS vol.84 (1998) pp.1196-1203. In the calculation example 1, a structure in which only the p-side compositionally graded layer 411 having a thickness of 260 nm was provided as the first portion 41 was used, and in the calculation examples 2 to 5, a structure in which the p-side compositionally graded layer 411 and the p-side intermediate layer 412 were provided as the first portion 41 was used. The thicknesses of the p-side intermediate layer 412 in the calculation examples 2 to 5 were 50 nm, 100 nm, 200 nm, and 400 nm, respectively. That is, the thicknesses of the first portion 41 in the calculation examples 1 to 5 were 260 nm, 310 nm, 360 nm, 460 nm, and 660 nm, respectively. The layer structure other than the first portion 41 is generally the same as that of the semiconductor laser device 100 of Example 1 described later, except that the second n-side optical guide layer 27 is changed from GaN to In. 0.05 Ga 0.95 N. The layer structure other than the first portion 41 is the same in calculation examples 1 to 3, and calculation examples 4 and 5 are the same as calculation examples 1 to 3 except that the film thickness of the first n-side light guiding layer 26 is two-thirds. The film thickness of the first n-side light guiding layer 26 in calculation examples 4 and 5 is made thinner in order to correct the shift of the peak of the electric field intensity from the active layer 3 caused by making the first portion 41 thicker.

[0020] FIG. 7 shows the relationship between the thickness of the first portion 41 and the proportion of leaked light to the second portion 43 for calculation examples 1 to 5. As shown in FIG. 7, the thicker the first portion 41 is, the less leaked light to the second portion 43 is, and the degree of the decrease becomes gentler from a thickness of about 400 nm. For this reason, it is preferable that the thickness of the first portion 41 is 400 nm or more. This makes it possible to reduce the leaked light to the second portion 43 to, for example, less than 3%.

[0021] (Semiconductor laser element 100) As shown in FIG. 2A, the semiconductor laser element 100 has a substrate 1, and an n-side semiconductor layer 2, an active layer 3, and a p-side semiconductor layer 4 provided thereon. The semiconductor laser element 100 is an edge-emitting laser element having a light-emitting end face and a light-reflecting end face intersecting with the main surface of a semiconductor layer such as the active layer 3. A ridge 4a is provided on the upper side of the p-side semiconductor layer 4. The ridge 4a has a mesa structure. The shape of the ridge 4a when viewed from above is long in the direction connecting the light-emitting end face and the light-reflecting end face, and is, for example, a rectangular shape with a short side parallel to the light-reflecting end face and a long side perpendicular to the light-reflecting end face. The part of the active layer 3 directly below the ridge 4a and its vicinity is an optical waveguide region. An insulating film 5 can be provided on the side surface of the ridge 4a and on the surface of the p-side semiconductor layer 4 continuing from the side surface of the ridge 4a. The substrate 1 is made of, for example, an n-type semiconductor, and an n-electrode 8 is provided on the lower surface thereof. Furthermore, a p-electrode 6 is provided in contact with the upper surface of the ridge 4a, and a p-side pad electrode 7 is further provided thereon.

[0022] The semiconductor laser device 100 can have a structure that oscillates laser light in the long wavelength range. The semiconductor laser element 100 can oscillate laser light in the green wavelength band, for example, laser light with a wavelength of 530 nm or more. That is, it can oscillate laser light with a peak wavelength of 530 nm or more. As the oscillation wavelength becomes longer from the blue wavelength band to the green wavelength band, the amount of leakage light outside the optical guide layer increases due to the effect of wavelength dispersion of the refractive index. As a result, the threshold current increases, and the current density during laser oscillation increases. And, the higher the current density, the larger the effective transition interval is expanded by shielding of the localized level and band filling, and the oscillation wavelength shifts to a shorter wavelength. By providing the p-side composition graded layer 411, it is possible to reduce the laser oscillation threshold current density as described later, and to suppress the short wavelength shift. In addition, since the refractive index difference between the cladding layer and the active layer is difficult to obtain due to the effect of wavelength dispersion of the refractive index, the threshold current density is still higher and the slope efficiency is also lower than that of the semiconductor laser element in the blue wavelength band. For this reason, if the configuration of this embodiment is adopted in the semiconductor laser element in the green wavelength band, the effect of improving efficiency due to the reduction of the optical absorption loss in the p-type semiconductor layer can be expected. Incidentally, the optical absorption loss in the p-type semiconductor layer can occur regardless of the wavelength of the laser light oscillated by the semiconductor laser element 100. Therefore, the wavelength of the laser light oscillated by the semiconductor laser element 100 is not limited to the green wavelength band, and may be, for example, the blue wavelength band.

[0023] (Substrate 1) The substrate 1 may be, for example, a nitride semiconductor substrate made of GaN or the like. The n-side semiconductor layer 2, active layer 3, and p-side semiconductor layer 4 grown on the substrate 1 may be semiconductors grown substantially in the c-axis direction. For example, a GaN substrate having a +c plane ((0001) plane) as the main surface may be used, and each semiconductor layer may be grown on the +c plane. Here, the +c plane as the main surface may include a surface having an off-angle of about ±1 degree or less. By using a substrate having a +c plane as the main surface, it is possible to obtain the advantage of excellent mass productivity.

[0024] (n-side semiconductor layer 2) The n-side semiconductor layer 2 can be a multi-layer structure made of a nitride semiconductor such as GaN, InGaN, or AlGaN. The n-side semiconductor layer 2 includes one or more n-type semiconductor layers. An example of the n-type semiconductor layer is a layer made of a nitride semiconductor containing n-type impurities such as Si or Ge. The n-side semiconductor layer 2 can have an n-side cladding layer and an n-side optical guide layer, and may include other layers. The n-side cladding layer has a larger band gap energy than the n-side optical guide layer. Although not as much as the p-type impurities, the n-type impurities also cause light absorption, so it is preferable that the n-side optical guide layer is undoped or has a lower n-type impurity concentration than the n-side cladding layer.

[0025] Fig. 4 shows an example of the layer structure of the n-side semiconductor layer 2. The n-side semiconductor layer 2 shown in Fig. 4 has, in order from the substrate 1 side, an underlayer 21, a first n-side cladding layer 22, a crack prevention layer 23, an intermediate layer 24, a second n-side cladding layer 25, a first n-side light guide layer 26, a second n-side light guide layer 27, and a hole blocking layer 28. The hole blocking layer 28 has a first hole blocking layer 281 and a second hole blocking layer 282.

[0026] The underlayer 21 to the first n-side light guide layer 26 are doped with n-type impurities. The underlayer 21 is, for example, an n-type AlGaN layer. The first n-side cladding layer 22 is, for example, a layer having a larger band gap energy than the underlayer 21 and doped with n-type impurities. The crack prevention layer 23 is, for example, made of InGaN, and its band gap energy is smaller than that of the well layer in the active layer 3. By providing the crack prevention layer 23, the probability of cracks occurring can be reduced. The intermediate layer 24 has a lattice constant between the crack prevention layer 23 and the second n-side cladding layer 25, and is made of, for example, GaN. When the crack prevention layer 23 is an InGaN layer, it is preferable to form the intermediate layer 24 of a GaN layer before growing the second n-side cladding layer 25. If the second n-side cladding layer 25 is grown in contact with the upper surface of the crack prevention layer 23, a part of the crack prevention layer 23 may be decomposed, which may affect the growth of the active layer 3, but by providing the intermediate layer 24, the probability of such decomposition occurring can be reduced. The intermediate layer 24 is provided with a thickness smaller than that of the crack prevention layer 23, for example. The second n-side cladding layer 25 is, for example, a layer having a band gap energy larger than that of the underlayer 21, and may be the same as that of the first n-side cladding layer 22. The first n-side cladding layer 22 and the second n-side cladding layer 25 are made of, for example, AlGaN. Either or both of the first n-side cladding layer 22 and the second n-side cladding layer 25 may have the maximum band gap energy in the n-side semiconductor layer 2. The first n-side cladding layer 22 and the second n-side cladding layer 25 may have the same composition and / or n-type impurity concentration. The n-side cladding layer may be a single layer, in which case the crack prevention layer may not be provided or may be provided above or below the n-side cladding layer.

[0027] The first n-side light guide layer 26 has a smaller band gap energy and a smaller n-type impurity concentration than the first n-side cladding layer 22 and the second n-side cladding layer 25. The first n-side light guide layer 26 is made of, for example, GaN. The band gap energy of the second n-side light guide layer 27 is larger than that of the well layer in the active layer 3 and smaller than that of the first n-side light guide layer 26. Since the second n-side light guide layer 27 is located closer to the active layer 3 than the first n-side light guide layer 26, it is preferable for the second n-side light guide layer 27 to have a smaller n-type impurity concentration than the first n-side light guide layer 26 in order to reduce optical absorption loss. The second n-side light guide layer 27 is made of, for example, undoped InGaN.

[0028] The second n-side light guide layer 27 may be a compositionally graded layer whose band gap energy becomes smaller as it approaches the active layer 3. When a compositionally graded layer is provided as the n-side light guide layer, the layer is made to have a stepwise change in composition so that the refractive index becomes higher as it approaches the active layer 3. This allows the n-side compositionally graded layer to continuously form a barrier for the optical waveguide, thereby enhancing light confinement to the active layer 3. The average value of the compositionally graded layer can be used as a criterion for determining the magnitude relationship between the band gap energy and the impurity concentration of the compositionally graded layer and other layers. The average value of the compositionally graded layer refers to the sum of the multiplication of the band gap energy, etc., and the film thickness of each sublayer constituting the compositionally graded layer, divided by the total film thickness. When a compositionally graded layer whose lattice constant becomes larger as it approaches the active layer 3 is provided in the n-side semiconductor layer 2, it is preferable to add an n-type impurity to the compositionally graded layer. In other words, the compositionally graded layer can be said to be composed of multiple sublayers whose compositions are slightly different from each other. For this reason, in the compositionally graded layer, it is difficult to avoid the generation of fixed charges even if the composition change rate is reduced. By adding n-type impurities, the fixed charges can be shielded, thereby reducing the degree of voltage rise caused by the generation of fixed charges.

[0029] It is preferable that at least a part of the hole blocking layer 28 contains n-type impurities. This makes it possible to block holes more efficiently. For example, the first hole blocking layer 281 is made of GaN, and the second hole blocking layer 282 is made of InGaN.

[0030] (Active layer 3) The active layer 3 can have a multi-layer structure made of nitride semiconductor layers such as GaN, InGaN, etc. The active layer 3 has a single quantum well structure or a multiple quantum well structure. It is considered that a multiple quantum well structure can easily obtain a sufficient gain compared to a single quantum well structure. When the active layer 3 has a multiple quantum well structure, it has multiple well layers and intermediate barrier layers sandwiched between the well layers. For example, the active layer 3 includes, in order from the n-side semiconductor layer 2 side, a well layer, an intermediate barrier layer, and a well layer. An n-side barrier layer 31 may be provided between the n-side semiconductor layer 2 and the well layer closest to the n-side semiconductor layer 2. The n-side barrier layer 31 may function as a part of the hole blocking layer 28. The n-side barrier layer 31 may be omitted, and the hole blocking layer 28 or the n-side light guide layer (the second n-side light guide layer 27) may function as the n-side barrier layer. Similarly, a p-side barrier layer may be provided between the well layer closest to the p-side semiconductor layer 4 and the p-side semiconductor layer 4. When the p-side barrier layer is not provided or is thin, a part of the p-side semiconductor layer 4 may function as the p-side barrier layer. When the p-side barrier layer is provided in the active layer 3, the thickness of the p-side barrier layer may be, for example, 5 nm or less. In other words, the shortest distance between the p-side semiconductor layer 4 and the well layer in the active layer 3 is, for example, 5 nm or less. As described above, the addition of p-type impurities increases the optical absorption loss, so it is preferable to form the active layer 3 without adding p-type impurities. Each layer of the active layer 3 is, for example, an undoped layer.

[0031] In when used as a semiconductor laser element with an oscillation wavelength of 530 nm or more x Ga 1-x The In composition ratio x of the N well layer is, for example, 0.25 or more, although it may increase or decrease depending on the layer structure other than the active layer 3. The upper limit of the In composition ratio x of the well layer is, for example, 0.50 or less. In this case, the oscillation wavelength of the semiconductor laser element is considered to be about 600 nm or less.

[0032] (p-side semiconductor layer 4) The p-side semiconductor layer 4 may have a multi-layer structure made of a nitride semiconductor such as GaN, InGaN, or AlGaN. The p-side semiconductor layer 4 may have a p-side cladding layer and a p-side optical guide layer, and may also include other layers. When a transparent conductive film is provided as the p-electrode 6, it is possible to make the transparent conductive film function as a cladding layer, so that a cladding layer does not have to be provided in the p-side semiconductor layer 4.

[0033] The p-side semiconductor layer 4 includes one or more p-type semiconductor layers. An example of the p-type semiconductor layer is a layer made of a nitride semiconductor containing p-type impurities such as Mg. Since the activation rate of p-type impurities is lower than that of n-type impurities such as Si, the free carrier absorption loss due to the p-type impurities increases in the p-type semiconductor layer. The larger the absorption loss, the lower the slope efficiency of the semiconductor laser device 100. In general, the internal loss α i is the free carrier absorption loss α fc includes the free carrier absorption loss α fc The internal losses other than α int Then, the threshold mode gain required for laser oscillation is expressed by the following model equation, which depends on the free carrier absorption loss. Here, α fc , α i and α m are the free carrier absorption loss, the average internal loss, and the mirror loss, respectively. For convenience, the mode distribution is not taken into consideration and the averages are expressed. Γ is the optical confinement factor in the active region, and g th denotes the threshold gain for laser oscillation. Γ th = α fc +α int +α m

[0034] The free carrier absorption loss here includes losses other than those in the active layer 3. For example, in a p-type semiconductor layer, the coefficient σ reflecting the p-type impurity concentration n and the free carrier absorption cross section fc and the average leakage light into the p-type semiconductor layer, Γ p In other words, even if the impurity concentration of the p-type semiconductor layer is the same, if the leakage light to the p-type semiconductor layer increases, the free carrier absorption loss α fc Similarly, even if the leakage light to the p-type semiconductor layer is the same, the free carrier absorption loss α fc The free carrier absorption loss α increases because of the concern that the driving voltage will increase significantly if the p-type impurity concentration is reduced. fc In order to reduce this, it is particularly effective to reduce the leakage of light into layers with a high p-type impurity concentration. α fc= n × σ fc ×Γ p

[0035] In addition, from the above formula, the increase in the leakage light to the p-type cladding layer increases the free carrier absorption loss, so the threshold gain g th It can be seen that the laser oscillation occurs when the internal structure of the laser cavity is in a state where g = g th In this steady state, the modal gain depends monotonically on the carrier density, so the carrier density above the laser oscillation threshold current is the threshold carrier density N th The higher the injected carrier density, the more likely it is that the localized level is blocked, the larger the effective band gap becomes, and the more likely it is that the laser oscillation wavelength shifts to the short wavelength side. fc This reduces the threshold gain g at lower currents. th By reaching the threshold current density j th The threshold carrier density N th can be reduced. This reduces the injected carrier density, suppresses the blocking of the localized level, and enables laser oscillation on the longer wavelength side. Therefore, from this point of view, it is particularly preferable to reduce the free carrier absorption loss in the semiconductor laser element 100 capable of oscillating laser light of a long wavelength, for example, 530 nm or more. It can also be said that there is an advantage in that a laser light source with a low threshold current can be obtained even in a semiconductor laser element on the shorter wavelength side.

[0036] Although the suppression of the shielding of the localized level has been described here, the same applies to the suppression of the band-filling effect. That is, the band-filling effect, in which the quasi-Fermi level moves away from the band edge due to current injection and the effective transition interval widens, also causes a short wavelength shift, but the free carrier absorption loss α fc This can also be suppressed by lowering the threshold carrier density by lowering

[0037] (Part 1 41) The first portion 41 is a portion of the p-side semiconductor layer 4 that connects between the active layer 3 and the p-type impurity-containing layer. The first portion 41 is a portion that does not contain a p-type semiconductor layer. If the p-type impurity concentration and film thickness are such that they do not affect the free carrier absorption loss, it may be acceptable for a part of the first portion 41 to contain a p-type impurity-containing layer. However, when doping with Mg, which is necessary to make it p-type, a doping amount of 1×10 18 / cm 3 A p-type impurity of about 400 nm or more is necessary, and in this case, there is a high possibility that free carrier absorption loss will increase. Therefore, it is preferable that the first portion 41 is a portion that does not contain a p-type semiconductor layer. It is preferable that the p-type impurity concentration of the first portion 41 is low enough that p-type impurities are not detected by analysis such as SIMS throughout the first portion 41. For example, the first portion 41 is formed without intentionally adding p-type impurities throughout the first portion 41 during manufacturing. As described above, the thicker the first portion 41 is, the more light leakage to the second portion 43 can be reduced, so the thickness of the first portion 41 is preferably 400 nm or more. The upper limit of the thickness of the first portion 41 can be set to a level at which the supply of holes from the second portion 43 is not hindered. In addition, as shown in Experimental Result 3 described later, the thicker the first portion 41 is, the more electrons overflow, so from this viewpoint, it is preferable that the thickness of the first portion 41 is thin. The thickness of the first portion 41 can be, for example, 660 nm or less. Furthermore, the first portion 41 can reduce the probability of electron overflow due to the band gap difference between it and the electron barrier layer 42. For this reason, it is preferable that the first portion 41 has a layer having a smaller band gap energy than the electron barrier layer 42 as a layer in contact with the electron barrier layer 42.

[0038] When the first portion 41 is a lightly doped portion rather than an undoped portion, it is preferable that the p-type impurity concentration throughout the first portion 41 is lower than the p-type impurity concentration of the electron barrier layer 42, and more preferably lower than the p-type impurity concentrations of both the electron barrier layer 42 and the second portion 43. The n-type impurity concentration of the first portion 41 is preferably 2×10 18 / cm 3Preferably, the first portion 41 has an n-type impurity concentration that is low enough that n-type impurities are not detected by SIMS analysis (i.e., background level). In other words, it is preferable that the first portion 41 does not substantially contain n-type impurities.

[0039] (p-side composition gradient layer 411, p-side intermediate layer 412) As shown in FIG. 2A, the first portion 41 can have a p-side compositionally graded layer 411 and a p-side intermediate layer 412. The p-side intermediate layer 412 is provided above the p-side compositionally graded layer 411. The p-side intermediate layer 412 may be disposed in contact with the upper surface of the p-side compositionally graded layer 411, or may be disposed in contact with the lower surface of the electron barrier layer 42. The structure of the first portion 41 is not limited to having both the p-side compositionally graded layer 411 and the p-side intermediate layer 412, but as described above, the p-side compositionally graded layer 411 can enhance light confinement to the active layer 3, and the p-side intermediate layer 412 can further increase the thickness of the first portion 41. The p-side compositionally graded layer 411 enhances light confinement to the active layer 3, thereby reducing the laser oscillation threshold current density. This can suppress the shielding of the localized level and suppress the short-wavelength shift of the oscillation wavelength due to increased current injection, which is advantageous for increasing the oscillation wavelength.

[0040] The p-side compositionally graded layer 411 is a layer whose band gap energy increases toward the top. The p-side compositionally graded layer 411 has an upper surface and a lower surface, and its band gap energy increases from the lower surface toward the upper surface. The band gap energy on the lower surface side is smaller than that on the upper surface side. In FIG. 2A, the p-side compositionally graded layer 411 is shown as a slope, but as described later, a compositionally graded layer can be said to be a collection of multiple sublayers having different compositions, so that the band gap energy in the p-side compositionally graded layer 411 increases in a step-like manner from the lower surface to the upper surface. An n-side compositionally graded layer that pairs with the p-side compositionally graded layer 411 may be provided in the n-side semiconductor layer 2. An example of such an n-side compositionally graded layer is a layer whose band gap energy decreases toward the active layer 3. For example, the p-side compositionally graded layer 411 and the n-side compositionally graded layer are formed symmetrically with respect to the active layer 3. By providing compositionally graded layers on both sides of the active layer 3 in this way, light can be confined in a balanced manner from both sides of the active layer 3. In order to improve the light confinement effect of the p-side compositional graded layer 411, the p-side compositional graded layer 411 is preferably disposed near the active layer 3. For this reason, the p-side compositional graded layer 411 is preferably disposed in contact with the active layer 3. In addition, the shortest distance between the p-side compositional graded layer 411 and the well layer 32 in the active layer 3 is preferably 5 nm or less.

[0041] The p-side compositionally graded layer 411 functions as, for example, a p-side optical guide layer. The film thickness of the p-side compositionally graded layer 411 is thicker than the film thickness of the well layer 32, and is also thicker than the film thickness of the p-side barrier layer 34 when the p-side barrier layer 34 is present. In order to improve the light confinement effect, the film thickness of the p-side compositionally graded layer 411 is preferably 200 nm or more. The film thickness of the p-side compositionally graded layer 411 can be 500 nm or less, preferably 350 nm or less, and more preferably 300 nm or less. When the p-side barrier layer 34 is provided, the bandgap energy at the lower end of the p-side compositionally graded layer 411 is preferably smaller than the bandgap energy of the p-side barrier layer 34. The bandgap energy at the upper end of the p-side compositionally graded layer 411 may have a bandgap energy equal to or higher than that of the p-side barrier layer 34. The p-side compositionally graded layer 411 preferably has a structure in which the refractive index monotonically decreases from the active layer 3 side toward the electron barrier layer 42 side and the bandgap energy monotonically increases from the active layer 3 side toward the electron barrier layer 42 side in order to suppress the overflow of electrons while attracting light to the active layer 3.

[0042] As shown in FIG. 5, the p-side compositionally graded layer 411 can be said to be composed of a plurality of sub-layers 411a, 411b, 411c, 411y, 411z having different compositions from each other. FIG. 5 is a partially enlarged view of the p-side compositionally graded layer 411 and its vicinity, and there are a large number of sub-layers other than those explicitly shown between the sub-layer 411c and the sub-layer 411y. When the p-side compositionally graded layer 411 is made of InGaN or GaN, the lowermost sub-layer 411a of the p-side compositionally graded layer 411 is composed of In a Ga 1-a N (0 < a < 1), and the uppermost sub-layer 411z of the p-side compositionally graded layer 411 is composed of In z Ga 1-zIt consists of N(0≦z<a). The upper limit value of the In composition ratio a is, for example, 0.25. Considering the suppression of the deterioration of crystallinity, the In composition ratio a is preferably 0.1 or less. Also, the lattice constant difference between adjacent sub-layers is preferably small. Thereby, the strain can be reduced. For this purpose, it is preferable that the p-side composition gradient layer 411 changes the composition little by little with a thin thickness. Specifically, in the p-side composition gradient layer 411, the In composition ratio preferably decreases for each film thickness of 25 nm or less from the lower surface to the upper surface. That is, the film thickness of each sub-layer 411a, 411b, 411c, 411y, 411z is preferably 25 nm or less. Furthermore, the film thickness of each sub-layer 411a, 411b, 411c, 411y, 411z is preferably 20 nm or less. The lower limit value of the film thickness of each sub-layer 411a, 411b, 411c, 411y, 411z is about 1 atomic layer (about 0.25 nm), for example. Also, the difference in the In composition ratio between adjacent sub-layers (for example, sub-layer 411a and sub-layer 411b) is preferably 0.005 or less. More preferably, it is 0.001 or less. The lower limit value is about 0.00007, for example.

[0043] Such a range is preferably satisfied throughout the entire p-side composition gradient layer 411. That is, it is preferable that all sub-layers are within such a range. For example, in the p-side composition gradient layer 411 with a film thickness of 260 nm, when the lowermost sub-layer 411a is In 0.05 Ga 0.95 N and the uppermost sub-layer 411z is GaN, it is grown under manufacturing conditions in which the composition is gradually changed in 120 steps. The number of times the composition changes in the p-side composition gradient layer 411 is preferably 90 or more. The composition change rate of the p-side composition gradient layer 411 (that is, the difference in the composition ratio between adjacent sub-layers) may be constant or may vary throughout the entire p-side composition gradient layer 411. The composition change rate of the p-side composition gradient layer 411 is preferably 0.001 or less throughout the entire p-side composition gradient layer 411. When a composition gradient layer is provided on the n-side, the preferable ranges of its composition, composition change rate, and film thickness can be the same as those of the p-side composition gradient layer 411.

[0044] It is preferable that the lower end of the ridge 4a is not located in the p-side compositional gradient layer 411. If the lower end of the ridge 4a is located in the p-side compositional gradient layer 411, the effective refractive index difference between the inside and outside of the ridge 4a varies greatly due to the variation in the depth of the ridge 4a. However, if the lower end of the ridge 4a is located in a layer of single composition, the variation in the effective refractive index difference between the inside and outside of the ridge 4a can be made smaller than that. For this reason, when the p-side compositional gradient layer 411 is provided, it is preferable to provide a layer of single composition for locating the lower end of the ridge 4a. This layer of single composition is preferably thicker than the variation in the depth when the ridge 4a is formed. As a result, even if the depth of the ridge 4a varies, the lower end of the ridge 4a can be located in the layer of single composition, so that the variation in the effective refractive index difference between the inside and outside of the ridge 4a can be made smaller. The thickness of such a layer of single composition for locating the lower end of the ridge 4a is preferably thicker than the sub-layers constituting the compositional gradient layer, and can be made thicker than 25 nm, for example. The thickness of the layer of single composition can be, for example, 600 nm or less. A layer of a single composition refers to a layer formed without intentionally varying the composition.

[0045] The p-side intermediate layer 412 can be provided as a layer of such a single composition. The p-side intermediate layer 412 may also have a multi-layer structure. When the p-side intermediate layer 412 has a multi-layer structure, at least the layer of the p-side intermediate layer 412 where the lower end of the ridge 4a is located should be a layer of a single composition. When the p-side intermediate layer 412 has a multi-layer structure, as shown in FIG. 2B, the p-side intermediate layer 412 may have a first layer 412A and a second layer 412B. The first layer 412A has a band gap energy that is larger than the average band gap energy of the p-side composition graded layer 411 and smaller than the band gap energy of the electron barrier layer 42. The second layer 412B has a band gap energy that is larger than the band gap energy of the first layer 412A and smaller than the band gap energy of the electron barrier layer 42. The first layer 412A and the second layer 412B are undoped. In addition, the refractive indexes may be smaller in the order of the average refractive index of the p-side composition graded layer 411, the refractive index of the first layer 412A, and the refractive index of the second layer 412B. In this specification, the average band gap energy refers to the sum of the multiplication of the band gap energy and the film thickness of each layer divided by the total film thickness. In the compositionally graded layer, the band gap energy of each of the sublayers constituting the layer is multiplied by its thickness, and the sum is divided by the total thickness to determine the average band gap energy of the compositionally graded layer. The same applies to the average refractive index and the average composition ratio.

[0046] By providing the second layer 412B, it is possible to reduce the leakage of light to the second portion 43, and to reduce the free carrier absorption loss occurring in the second portion 43. By providing the second layer 412B having a lower refractive index than the first layer 412A as the p-side intermediate layer 412, it is possible to reduce the film thickness of the p-side intermediate layer 412 required to obtain the same degree of light confinement effect, compared to the case where the p-side intermediate layer 412 is composed of only the first layer 412A. As described above, it is preferable that the thickness of the first portion 41 is thick in order to reduce the leakage of light to the second portion 43, but on the other hand, it is effective to reduce the thickness of the first portion 41 in order to further reduce the voltage. By providing the p-side compositionally graded layer 411 and the second layer 412B, it is possible to suppress the voltage rise while reducing the leakage of light to the second portion 43.

[0047] When the first layer 412A and the second layer 412B are each a layer of a single composition, it is preferable that the lower end of the ridge 4a is located in the first layer 412A or the second layer 412B. As described above, this makes it possible to reduce the variation in the effective refractive index difference between the inside and outside of the ridge 4a even if the position of the lower end of the ridge 4a varies during manufacturing. The lower end of the ridge 4a may be located in the first layer 412A as shown in FIG. 2B and FIG. 2C, or may be located in the second layer 412B as shown in FIG. 2D. The first layer 412A is, for example, a GaN layer. The second layer 412B is, for example, an AlGaN layer. In this case, the Al composition ratio of the second layer 412B can be, for example, 0.01% or more and 10% or less. The film thickness of the second layer 412B can be 1 nm or more and 600 nm or less. When the refractive index of the second layer 412B is smaller than that of the first layer 412A, the thickness of the second layer 412B is preferably thicker than that of the first layer 412A. This can further strengthen the light confinement in the active layer 3. For example, the thickness of the second layer 412B is made 50 nm or more thicker than that of the first layer 412A. In this case, the first layer 412A has less effect on the light confinement than the p-side composition gradient layer 411 and the second layer 412B, so by making the thickness of the first layer 412A thinner, it is possible to reduce the electrons overflowing from the active layer 3 while reducing the light leakage to the second portion 43. This can improve the slope efficiency of the semiconductor laser element. From this viewpoint, the thickness of the first layer 412A is preferably 100 nm or less, more preferably 50 nm or less. In addition, the thickness of the first layer 412A is preferably half or less, more preferably one-fourth or less, of the thickness of the second layer 412B. The thickness of the first layer 412A may be 1 nm or more.

[0048] As shown in FIG. 2B, the second layer 412B may have a band gap energy larger than the band gap energy of a layer (lower p-type semiconductor layer 431 in FIG. 2B) in contact with the electron barrier layer 42 in the second portion 43. By providing a layer with a relatively large band gap energy in the first portion 41 in this way, it is considered that there is an advantage in that it is possible to reduce light leakage to the second portion 43, which is a portion with a larger absorption loss than the first portion 41. In this case, it is preferable to use a material that functions as a cladding layer for the p-electrode 6. This makes it unnecessary to provide a p-type cladding layer in the second portion 43, so that the voltage when a bias is applied can be reduced. These will be described in detail below.

[0049] First, when the p-electrode 6 is made to function as a cladding layer, a light-transmitting material is used as the p-electrode 6, but even light-transmitting materials can cause absorption loss. For this reason, if there is a lot of light leakage to the p-electrode 6 and it is desired to reduce this, a layer that functions as a p-type cladding layer, for example, a p-type layer containing Al, is provided in the second portion 43. In order to function as a p-type cladding layer, it is preferable that the Al composition ratio is relatively large, but on the other hand, the activation energy required to activate the p-type impurity of the layer increases as the Al composition ratio is increased. If the second portion 43 is not sufficiently p-typed, the series resistance increases and the voltage when a bias is applied increases, so when a p-type cladding layer is provided in the second portion 43, the acceptor concentration is increased, for example, by increasing the amount of p-type impurity added. However, as described above, if the amount of p-type impurity added increases, the light absorption loss increases and the light output decreases. If an undoped AlGaN layer is provided between the active layer 3 and the electron barrier layer 42 as shown in FIG. 2B, this AlGaN layer does not need to be p-typed, so even if the Al composition ratio is increased, the voltage is less likely to increase. In addition, since it is an undoped AlGaN layer, the optical absorption loss is unlikely to increase. Generally, an undoped layer is a high-resistance layer, and when it is provided, the voltage tends to increase, but providing an undoped AlGaN layer in the first portion 41 is different from the general tendency. This is because the undoped AlGaN layer disposed between the active layer 3 and the electron barrier layer 42 is dominated by donors when a bias is applied, and acceptors having activation energy larger than that of the donors function as minority carriers. Therefore, an AlGaN layer having a relatively large Al composition ratio, such as the second layer 412B, can be provided in the first portion 41. In other words, a layer having a large band gap energy can be provided in the first portion 41. By providing such a layer, it is possible to reduce light leakage to the second portion 43, so that it is not necessary to provide a p-type cladding layer in the second portion 43. That is, the Al composition ratio of the second portion 43 can be reduced. This makes it possible to reduce the series resistance of the second portion 43 and reduce the voltage of the semiconductor laser device 100.

[0050] 3A to 3C are schematic diagrams showing examples of the relationship between the band gap energy of the top layer of the first portion 41, the electron barrier layer 42, and the bottom layer of the second portion 43. The top layer of the first portion 41 is in contact with the bottom surface of the electron barrier layer 42, and the bottom layer of the second portion 43 is in contact with the top surface of the electron barrier layer 42. In FIG. 3A, the band gap energy of the bottom layer is smaller than that of the top layer. In FIG. 3B, the band gap energy of the bottom layer is equal to that of the top layer. In FIG. 3C, the band gap energy of the bottom layer is larger than that of the top layer. For the above-mentioned reasons, as shown in FIG. 3A, it is preferable that the band gap energy of the bottom layer (e.g., the lower p-type semiconductor layer 431) of the second portion 43 is smaller than that of the top layer (e.g., the second layer 412B) of the first portion 41. This can reduce light leakage to the second portion 43, and is suitable for a configuration in which a material that functions as a cladding layer is used for the p-electrode 6. In this configuration, the voltage when applying a bias to the semiconductor laser element 100 can be reduced. Regarding the magnitude relationship of the band gap energies, when the uppermost layer and / or the lowermost layer is a layer in which the band gap energy is not constant, such as a superlattice layer or a compositionally graded layer, the magnitude relationship may be compared using the average band gap energy. In the case of a superlattice layer, the band gap energy of each sublayer constituting the superlattice layer is multiplied by the film thickness, and the sum is divided by the total film thickness of the superlattice layer to obtain the average band gap energy of the superlattice layer. When the uppermost layer and the lowermost layer are AlGaN layers, the magnitude relationship of these band gap energies can be rephrased as the magnitude relationship of the Al composition ratio.

[0051] The bottom layer may be an AlGaN layer having an Al composition ratio of 4% or less. The bottom layer may be a layer having an Al composition ratio of substantially zero, that is, a GaN layer. The bottom layer may be, for example, a p-type semiconductor layer containing a p-type impurity such as Mg. The bottom layer may be a quaternary layer such as AlInGaN. The second portion 43 including the bottom layer preferably has an average Al composition ratio of 4% or less in order to reduce the voltage. The top layer provided in the first portion 41 preferably contains 0.01% or more Al in part or in whole. More preferably, the average Al composition ratio of the top layer is made greater than 4%. The top layer may have a band gap energy larger than any of the band gap energies of the layers (which may be single layers) constituting the second portion 43. The top layer may be a superlattice layer or a compositionally graded layer containing AlGaN or AlInGaN. Note that one or more layers connecting the top layer to the active layer 3 may each have a band gap energy smaller than the band gap energy of the top layer. Such one or more layers are, for example, the first layer 412A and the p-side compositionally graded layer 411 shown in FIG. 2B, but are not limited to these layers.

[0052] The semiconductor laser element 100 may have the following configuration. The semiconductor laser element 100 includes an n-side semiconductor layer 2, an active layer 3, and a p-side semiconductor layer 4, each of which is made of a nitride semiconductor, in that order from top to bottom, and a ridge 4a protruding upward is provided on the p-side semiconductor layer 4. The p-side semiconductor layer 4 includes a first portion 41 that is arranged in contact with the upper surface of the active layer 3, has one or more semiconductor layers, and is undoped; an electron barrier layer 42 that is arranged in contact with the upper surface of the first portion 41, has a band gap energy larger than that of the first portion 41, and contains p-type impurities; and a second portion 43 that is arranged in contact with the upper surface of the electron barrier layer 42, and has one or more p-type semiconductor layers containing p-type impurities. The first portion 41 has a top layer that is in contact with the bottom surface of the electron barrier layer 42, and the second portion 43 has a bottom layer that is in contact with the top surface of the electron barrier layer 42, and the band gap energy of the bottom layer is smaller than that of the top layer. The bottom end of the ridge 4a is located in the first portion 41.

[0053] (Electron barrier layer 42) The electron barrier layer 42 contains a p-type impurity such as Mg. The band gap energy of the electron barrier layer 42 is larger than that of the first portion 41. When the first portion 41 has a multi-layer structure as described above, the electron barrier layer 42 is a layer having a band gap energy larger than that of any of the layers constituting the first portion 41. Since the electron barrier layer 42 is a layer having such a large band gap energy, the electron barrier layer 42 can function as a barrier against electrons overflowing from the active layer 3. The electron barrier layer 42 preferably has a band gap energy difference of 0.1 eV or more with respect to the uppermost layer of the first portion 41. The band gap energy difference between the electron barrier layer 42 and the uppermost layer of the first portion 41 can be, for example, 1 eV or less. The electron barrier layer 42 is, for example, a layer having the highest band gap energy in the p-side semiconductor layer 4. The electron barrier layer 42 may be a layer having a smaller film thickness than the p-side compositionally graded layer 411. The electron barrier layer 42 may have a multi-layer structure. In this case, the electron barrier layer 42 has a layer having a band gap energy larger than that of any of the layers constituting the first portion 41. For example, as shown in FIG. 2A etc., the first portion 41 or the electron barrier layer 42 may have a first electron barrier layer 42A and a second electron barrier layer 42B. When the first portion 41 or the electron barrier layer 42 has a superlattice layer, the magnitude relationship is compared using the average band gap energy of the superlattice layer, not the band gap energy of each layer constituting the superlattice layer. The electron barrier layer 42 is made of, for example, AlGaN. When the electron barrier layer 42 is made of AlGaN, its Al composition ratio may be 8 to 30%. The film thickness of the electron barrier layer 42 may be, for example, 5 nm or more and 100 nm or less.

[0054] As shown in FIGS. 2C and 2D, the shortest distance from the bottom surface of the ridge 4a to the electron barrier layer 42 is preferably greater than the shortest distance from the top surface of the ridge 4a to the electron barrier layer 42. This arrangement can move the peak of the light intensity away from the portion containing the p-type impurity such as the electron barrier layer 42, and can shorten the distance between the lower end of the ridge 4a and the active layer 3. The shortest distance from the bottom surface of the ridge 4a to the electron barrier layer 42 refers to the shortest distance from a virtual straight line connecting the lower ends of the ridge 4a to the lower surface of the electron barrier layer 42 in the cross-sectional view shown in FIG. 1. In other words, it can be said that the electron barrier layer 42 is located on the upper side of the ridge 4a. Also, if the shortest distance from the bottom surface of the ridge 4a to the active layer 3 is, for example, about 436 nm, a kink may occur in the IL characteristic curve. For this reason, it is preferable that the shortest distance from the bottom surface of the ridge 4a to the active layer 3 is 430 nm or less. This can strengthen the light confinement in the horizontal lateral direction.

[0055] (Second part 43) The second portion 43 has one or more p-type semiconductor layers containing p-type impurities. The concentration of the p-type impurities in the p-type semiconductor layers in the second portion 43 is, for example, 1×10 18 / cm 3 Can be more than 1×10 22 / cm 3 The thickness of the second portion 43 may be set to 260 nm or less. As described above, the driving voltage can be reduced by reducing the thickness of the second portion 43. Therefore, the thickness of the second portion 43 may be set to 10 nm or more. The second portion 43 may include an undoped layer. However, if there is an undoped layer in the second portion 43, the resistance of the second portion 43 will be higher than that of the undoped layer. Therefore, it is preferable that the entire second portion 43 contains p-type impurities. In the case of a superlattice layer, the average p-type impurity concentration can be regarded as the p-type impurity concentration of the superlattice layer. Therefore, when the second portion 43 has a superlattice layer, the superlattice layer may have a laminated structure of an undoped layer and a p-type impurity-containing layer.

[0056] As shown in FIG. 2A, the second portion 43 can have an upper p-type semiconductor layer 432 and a lower p-type semiconductor layer 431. The upper p-type semiconductor layer 432 forms the upper surface of the ridge 4a. That is, the upper p-type semiconductor layer 432 is the uppermost layer of the second portion 43 and the uppermost layer of the ridge 4a. The upper p-type semiconductor layer 432 functions as a p-side contact layer. The lower p-type semiconductor layer 431 is disposed between the upper p-type semiconductor layer 432 and the electron barrier layer 42, and has a band gap energy larger than that of the upper p-type semiconductor layer 432.

[0057] The lower p-type semiconductor layer 431 is made of, for example, AlGaN. The upper p-type semiconductor layer 432 is made of, for example, GaN. The lower p-type semiconductor layer 431 preferably has a band gap energy between the electron barrier layer 42 and the upper p-type semiconductor layer 432. Since AlGaN containing p-type impurities tends to have higher resistance than GaN containing p-type impurities, the upper p-type semiconductor layer 432 is preferably a GaN layer to which p-type impurities are added. By providing a lower p-type semiconductor layer made of AlGaN under the upper p-type semiconductor layer 432, it is possible to strengthen the light confinement in the active layer 3 compared to the case where the second portion 43 is formed only of a GaN layer. In addition, since the Al composition ratio of the lower p-type semiconductor layer 431 is smaller than the Al composition ratio of the electron barrier layer 42, it is possible to make the lower p-type semiconductor layer 431 have a lower resistance than the electron barrier layer 42. The lower p-type semiconductor layer 431 may function as a p-side cladding layer. The lower p-type semiconductor layer 431 may be a p-type GaN layer, which can further reduce the resistance of the second portion 43. In this case, it is preferable to form the p-electrode from a material that functions as a cladding layer, such as ITO.

[0058] The upper p-type semiconductor layer 432 may have a thickness of, for example, 5 to 30 nm. The lower p-type semiconductor layer 431 may have a thickness of, for example, 1 to 260 nm. The lower p-type semiconductor layer 431 may have a thickness smaller than that of the p-side intermediate layer 412, and may further have a thickness smaller than that of the second layer 412B. The lower p-type semiconductor layer 431 and the second layer 412B may both be AlGaN layers, and may have the same Al composition ratio. The lower p-type semiconductor layer 431 has a thickness larger than that of, for example, the electron barrier layer 42. Therefore, in order to reduce free carrier absorption loss, it is preferable that the p-type impurity concentration of the lower p-type semiconductor layer 431 is lower than the p-type impurity concentration of the electron barrier layer 42.

[0059] (insulating film 5, n-electrode 8, p-electrode 6, p-side pad electrode 7) The insulating film 5 can be formed of a single layer or multilayer of oxides or nitrides of, for example, Si, Al, Zr, Ti, Nb, Ta, etc. The n-electrode 8 is provided, for example, on almost the entire lower surface of the n-type substrate 1. The p-electrode 6 is provided on the upper surface of the ridge 4a. When the width of the p-electrode 6 is narrow, a p-side pad electrode 7 wider than the p-electrode 6 is provided on the p-electrode 6, and a wire or the like may be connected to the p-side pad electrode 7. Examples of materials for each electrode include a single layer or multilayer of conductive oxides containing at least one selected from metals or alloys such as Ni, Rh, Cr, Au, W, Pt, Ti, and Al, Zn, In, and Sn. Examples of conductive oxides include ITO (Indium Tin Oxide), IZO (Indium Zinc Oxide), and GZO (Gallium-doped Zinc Oxide). The thickness of the electrodes may be such that they can usually function as electrodes of semiconductor elements. For example, the thickness may be about 0.1 μm to 2 μm.

[0060] The p-electrode 6 is preferably a transparent conductive film having a refractive index smaller than that of the active layer 3. This allows it to function as a cladding layer. Furthermore, the p-electrode 6 is preferably a transparent conductive film having a refractive index smaller than that of the second portion 43. This can provide a better light confinement effect. When the second portion 43 is provided with a p-side cladding layer, for example, an AlGaN layer having a relatively high Al composition ratio and doped with p-type impurities is provided as the p-side cladding layer, but the higher the Al composition ratio, the higher the resistance tends to be. If the p-electrode 6 functions as a cladding layer, it is not necessary to provide a p-side cladding layer in the second portion 43, or even if a p-side cladding layer is provided, its Al composition ratio can be lowered. This can reduce the resistance and the driving voltage of the semiconductor laser element 100. An example of the p-electrode 6 functioning as a cladding layer is the p-electrode 6 made of ITO.

[0061] (Manufacturing method) The manufacturing method of the semiconductor laser device 100 according to the embodiment may include steps S101 to S106 shown in the flow chart of FIG. 6A. In step S101, an n-side semiconductor layer 2 is formed on a substrate 1. In step S102, an active layer 3 is formed on the n-side semiconductor layer 2. In step S103, a first portion 41 having one or more semiconductor layers is formed undoped on the upper surface of the active layer 3. In step S104, an electron barrier layer 42 having a band gap energy larger than the band gap energy of the first portion 41 is formed on the upper surface of the first portion 41 by doping with p-type impurities. In step S105, a second portion 43 having one or more p-type semiconductor layers formed by doping with p-type impurities is formed on the upper surface of the electron barrier layer 42. In step S106, a part of the p-side semiconductor layer 4 including the first portion 41, the electron barrier layer 42, and the second portion 43 is removed to form a ridge 4a protruding upward. Through these steps, a semiconductor laser element 100 can be obtained that includes the n-side semiconductor layer 2, the active layer 3, and the p-side semiconductor layer 4 in this order, and that has the ridge 4a protruding upward from the p-side semiconductor layer 4. The effects and preferred configurations of the layers and the like obtained through each step are as described above. For example, as shown in FIG. 6B, the step S103 of forming the first portion 41 can include a step S103A of forming the p-side compositionally graded layer 411 in an undoped state, in which the band gap energy increases toward the top, and a step S103B of forming the p-side intermediate layer 412 in an undoped state above the p-side compositionally graded layer 411. In this case, in the step S106 of forming the ridge 4a, a part of the p-side semiconductor layer 4 can be removed so that the lower end of the ridge 4a is located in the p-side intermediate layer 412. In addition, in the step S105 of forming the second portion 43, the second portion 43 having a thickness smaller than that of the first portion 41 can be formed. In this case, in step S106 of forming the ridge 4a, a part of the p-side semiconductor layer 4 can be removed so that the lower end of the ridge 4a is located in the first portion 41. In addition, in step S105 of forming the second portion 43, a layer having a smaller band gap energy than the band gap energy of the uppermost layer of the first portion 41 may be formed as the lowermost layer of the second portion 43.

[0062] Example 1 As Example 1, a semiconductor laser element having a p-side semiconductor layer 4 shown in Fig. 2A and Fig. 4 was fabricated. An MOCVD apparatus was used to fabricate an epitaxial wafer that would become the semiconductor laser element. In addition, trimethylgallium (TMG), triethylgallium (TEG), trimethylaluminum (TMA), trimethylindium (TMI), ammonia (NH3), silane gas, and bis(cyclopentadienyl)magnesium (Cp2Mg) were appropriately used as raw materials.

[0063] An n-side semiconductor layer 2, an active layer 3, and a p-side semiconductor layer 4 were grown on an n-type GaN substrate (substrate 1) with the +c plane as the upper surface. First, as the n-side semiconductor layer 2, a 1.0 μm-thick Al 0.018 Ga 0.982 N layer (underlayer 21) and Al with Si added and a thickness of 250 nm 0.08 Ga 0.92 N layer (first n-side cladding layer 22) and a 150 nm thick In 0.04 Ga 0.96 The N layer (crack prevention layer 23), the GaN layer (intermediate layer 24) with a thickness of 10 nm and with Si added, and the Al layer (intermediate layer 25) with a thickness of 650 nm and with Si added 0.08 Ga 0.92 The first n-side optical guide layer 26 is an undoped InN layer (second n-side cladding layer 25), a GaN layer (first n-side optical guide layer 26) with a thickness of 200 nm and a Si-doped InN layer (second n-side cladding layer 25). 0.03 Ga 0.97 The n-type layer (second n-side light guide layer 27), a 1.2 nm-thick GaN layer (first hole blocking layer 281) doped with Si, and a 4 nm-thick In layer (second n-side light guide layer 27) doped with Si. 0.05 Ga 0.95 A layer (second hole blocking layer 282), and an N layer (second hole blocking layer 283) were grown in this order. Next, a GaN layer doped with Si (n-side barrier layer 31) and an undoped In 0.25 Ga 0.75 An N layer (well layer 32), an undoped GaN layer (intermediate barrier layer), and an undoped In 0.25 Ga 0.75An active layer 3 including an N layer (well layer 32) and an undoped GaN layer (p-side barrier layer 34) in this order was grown. Next, as the p-side semiconductor layer 4, an undoped compositionally graded layer (p-side compositionally graded layer 411) having a thickness of 260 nm, an undoped GaN layer (p-side intermediate layer 412) having a thickness of 200 nm, and an Al layer having a thickness of 3.9 nm and doped with Mg were formed. 0.10 Ga 0.90 N layer (first electron barrier layer 42A) and Mg-doped Al 0.16 Ga 0.84 N layer (second electron barrier layer 42B) and Mg-doped Al 0.04 Ga 0.96 An N layer (lower p-type semiconductor layer 431) and a 15 nm-thick GaN layer (upper p-type semiconductor layer 432) doped with Mg were grown in this order. The p-side compositionally graded layer 411 begins its growth at In. 0.05 Ga 0.95 The In composition was grown by substantially monotonically decreasing in 120 steps so that the composition gradient was nearly linear.

[0064] Then, the epitaxial wafer on which the above layers have been formed is removed from the MOCVD apparatus, and a ridge 4a, an insulating film 5, a p-electrode 6, a p-side pad electrode 7, and an n-electrode 8 are formed, and a reflective film is formed on each of the light-emitting end face and the light-reflecting end face. The epitaxial wafer is then singulated to obtain semiconductor laser elements 100. The depth of the ridge 4a was about 340 nm. That is, the ridge 4a was formed so that its lower end was located in the first layer 412A. In addition, an ITO film with a film thickness of 200 nm was formed as the p-electrode 6. The peak wavelength of the laser light emitted by the semiconductor laser device 100 in accordance with Example 1 was about 530 nm.

[0065] Example 2 As Example 2, a semiconductor laser device having a p-side semiconductor layer 4 shown in FIG. 2B was fabricated. That is, the p-side intermediate layer 412 is made of not only the first layer 412A but also an undoped Al layer having a thickness of 100 nm. 0.05 Ga 0.95A semiconductor laser element similar to that of Example 1 was fabricated, except that an N layer (second layer 412B) was also formed and the film thickness of the lower p-type semiconductor layer 431 was set to 200 nm.

[0066] Example 3 As Example 3, a semiconductor laser device having a p-side semiconductor layer 4 shown in FIG. 2C was fabricated. That is, a semiconductor laser element similar to that of Example 2 was fabricated, except that the thickness of second layer 412B was set to 200 nm and the thickness of lower p-type semiconductor layer 431 was set to 100 nm.

[0067] Example 4 As Example 4, a semiconductor laser element similar to Example 3 was fabricated, except that the thickness of the first layer 412A was set to 100 nm.

[0068] Example 5 As Example 5, a semiconductor laser element similar to Example 3 was fabricated, except that the thickness of the first layer 412A was set to 50 nm.

[0069] Example 6 As Example 6, a semiconductor laser device having a p-side semiconductor layer 4 shown in FIG. 2D was fabricated. In Example 6, a semiconductor laser element was fabricated similarly to Example 3, except that the depth of the ridge 4a was set to 270 nm. That is, the semiconductor laser elements of Examples 1 to 5 were formed so that the lower end of the ridge 4a was located in the first layer 412A, whereas the semiconductor laser element of Example 6 was formed so that the lower end of the ridge 4a was located in the second layer 412B.

[0070] (Comparative Examples 1 to 4) As Comparative Example 1, a semiconductor laser element similar to that of Example 1 was fabricated, except that the depth of the ridge 4a was set to 270 nm. That is, the semiconductor laser element of Comparative Example 1 was formed so that the lower end of the ridge 4a was located in the lower p-type semiconductor layer 431. Also, as Comparative Example 2 and Comparative Example 3, semiconductor laser elements similar to that of Comparative Example 1 were fabricated, except that the thickness of the p-side intermediate layer 412 was different. The thickness of the p-side intermediate layer 412 of Comparative Example 2 was set to 300 nm, and the thickness of the p-side intermediate layer 412 of Comparative Example 3 was set to 400 nm. As Comparative Example 4, a semiconductor laser element similar to that of Comparative Example 1 was fabricated, except that the p-side intermediate layer 412 was not provided. That is, in all of the semiconductor laser elements of Comparative Examples 1 to 4, the lower end of the ridge 4a was located in the lower p-type semiconductor layer 431, and the shortest distance from the active layer 3 to the electron barrier layer 42 was formed so that it became longer in the order of Comparative Example 4, Comparative Example 1, Comparative Example 2, and Comparative Example 3. The peak wavelength of the laser light emitted by the semiconductor laser elements of Comparative Examples 1 to 4 was about 525 nm.

[0071] (Experimental result 1) First, the IL characteristics of the semiconductor laser elements of Comparative Examples 1 to 4 are shown in FIG. 8. In the graph of FIG. 8, the horizontal axis indicates the current, and the vertical axis indicates the optical output. In FIG. 8, the thin solid line indicates Comparative Example 1, the thin dashed line indicates Comparative Example 2, the thick dashed line indicates Comparative Example 3, and the thick solid line indicates Comparative Example 4. As shown in FIG. 8, in Comparative Examples 1 to 4 in which the lower end of the ridge 4a is located above the electron barrier layer 42, the IL characteristics became more unstable as the shortest distance from the active layer 3 to the electron barrier layer 42 increased. Comparative Examples 1 and 2 had improved optical output and slope efficiency compared to Comparative Example 4, but a kink occurred in which a part of the IL characteristics graph was bent. In the semiconductor laser elements of Comparative Examples 1 and 2, the distance from the active layer 3 to the lower end of the ridge 4a was also longer due to the provision of the p-side intermediate layer 412, so that the effective refractive index difference between the inside and outside of the ridge 4a was reduced compared to Comparative Example 4. It is considered that this caused the horizontal-lateral mode to become unstable in the semiconductor laser elements of Comparative Examples 1 and 2, causing a kink. Moreover, the semiconductor laser element of Comparative Example 3, in which the p-side intermediate layer 412 was further thickened, not only exhibited kinks but also exhibited a lower optical output than the semiconductor laser element of Comparative Example 4. Thus, when the lower end of the ridge 4a was located above the electron barrier layer 42, even if an attempt was made to improve efficiency by providing the p-side intermediate layer 412, kinks occurred and other problems occurred that made the IL characteristics unstable.

[0072] (Experimental result 2) IL characteristics of the semiconductor laser elements of Examples 1 to 3 are shown in FIG. 9A, and IV characteristics are shown in FIG. 9B. In the graph of FIG. 9A, the horizontal axis indicates the current, and the vertical axis indicates the optical output. In the graph of FIG. 9B, the horizontal axis indicates the current, and the vertical axis indicates the voltage. In FIGS. 9A and 9B, the thin solid line indicates Example 1, the thick solid line indicates Example 2, and the dashed line indicates Example 3. First, Examples 1 to 3 are compared with Comparative Examples 1 to 3 using FIG. 8 and FIG. 9A. The shortest distance from the active layer 3 to the electron barrier layer 42 is the same in Example 1 and Comparative Example 1, the same in Example 2 and Comparative Example 2, and the same in Example 3 and Comparative Example 3. As can be seen from FIG. 8 and FIG. 9A, in Comparative Examples 1 to 3, the IL characteristics became more unstable as the distance from the active layer 3 to the electron barrier layer 42 was increased, but in Examples 1 to 3, the IL characteristics were almost the same regardless of the distance from the active layer 3 to the electron barrier layer 42. This is believed to be because the ridge 4a was formed deep in the semiconductor laser devices 100 of Examples 1 to 3, which strengthened the lateral optical confinement and stabilized the horizontal lateral mode. The optical output of Comparative Examples 1 to 3 is higher than that of Examples 1 to 3 because the oscillation wavelength of Comparative Examples 1 to 3 is shorter, and it cannot be said that the difference in optical output is caused by the difference in the depth of the ridge 4a.

[0073] In addition, the film thickness of the lower p-type semiconductor layer 431 is thinner in the order of Example 1, Example 2, and Example 3. However, as shown in FIG. 9B, it was confirmed that the voltage required to drive the semiconductor laser element 100 is reduced by making the lower p-type semiconductor layer 431 thinner. This is considered to be because the lower p-type semiconductor layer 431 is an AlGaN layer, which is a layer with a relatively high series resistance. The second layer 412B is also an AlGaN layer, and when such an undoped AlGaN layer is provided in the p-side semiconductor layer 4, the electrical resistance may increase and the probability of hole injection into the active layer 3 may decrease, but the results shown in FIG. 9A and FIG. 9B show no such effect. This is considered to be because the band of the second layer 412B is bent when a voltage is applied, which promotes hole injection. In addition, it is considered that electrons overflowing from the active layer 3 fill the first portion 41 when a voltage is applied.

[0074] (Experimental result 3) FIG. 10A shows the IL characteristics of the semiconductor laser devices of Examples 3 to 5, and FIG. 10B shows the IV characteristics. In the graph of FIG. 10A, the horizontal axis indicates the current, and the vertical axis indicates the optical output. In the graph of FIG. 10B, the horizontal axis indicates the current, and the vertical axis indicates the voltage. In FIGS. 10A and 10B, the dashed line indicates Example 3, the solid line indicates Example 4, and the dashed line indicates Example 5. The thickness of the first layer 412A decreases in the order of Example 3, Example 4, and Example 5, and as shown in FIG. 10A, it was confirmed that the slope efficiency is improved by decreasing the thickness of the first layer 412A. As described above, by moving the electron barrier layer 42 and the second portion 43 containing p-type impurities away from the active layer 3, it is possible to reduce the light leakage Γp to the second portion 43, which has a large free carrier absorption loss. However, on the other hand, the more the electron barrier layer 42 is moved away from the active layer 3, the more electrons overflow from the active layer 3. Therefore, by reducing the thickness of the first layer 412A, which has less effect on light confinement than the p-side composition gradient layer 411 and the second layer 412B, it is possible to suppress an increase in overflowing electrons while reducing the leakage of light to the second portion 43, which is considered to have improved the slope efficiency. Also, as shown in Fig. 10B, it was confirmed that the change in the thickness of the first layer 412A has almost no effect on the drive voltage.

[0075] (Experimental result 4) The IL characteristics of the semiconductor laser elements of Examples 3 and 6 are shown in Fig. 11A, and the IV characteristics are shown in Fig. 11B. In the graph of Fig. 11A, the horizontal axis represents current and the vertical axis represents optical output. In the graph of Fig. 11B, the horizontal axis represents current and the vertical axis represents voltage. In Figs. 11A and 11B, the dashed line represents Example 3 and the solid line represents Example 6. The depth of the ridge 4a is shallower in Example 6 than in Example 3, but as shown in Figs. 11A and 11B, both showed similar characteristics. [Explanation of symbols]

[0076] 100 Semiconductor laser element 1 Board 2 n-side semiconductor layer 21 Base layer 22 1st n-side cladding layer 23 Crack prevention layer 24 Middle Class 25 2nd n-side cladding layer 26 First n-side optical guide layer 27 Second n-side optical guide layer 28 Hole Block Layer 281 1st Hole Block Layer 282 2nd Hole Block Layer 3 Active layer 31 n-side barrier layer 32 Well Layer 34 p-side barrier layer 4 p-side semiconductor layer 41 Part 1 411 p-side compositionally graded layer 412 p side middle layer 412A 1st layer 412B 2nd layer 42 Electron Barrier Layer 42A First electron barrier layer 42B Second electron barrier layer 43 Part 2 431 Lower p-type semiconductor layer 432 Upper p-type semiconductor layer 4a Ridge 5. Insulating film 6p electrode 7 P-side pad electrode 8n electrode 411a, 411b, 411c, 411y, 411z sub-layers

Claims

1. A semiconductor laser element having, in order from top to top, an n-side semiconductor layer, an active layer, and a p-side semiconductor layer, each of which is made of a nitride semiconductor, and a ridge protruding upwardly from the p-side semiconductor layer, The p-side semiconductor layer is a first portion that is disposed in contact with an upper surface of the active layer, has one or more semiconductor layers, and is undoped; an electron barrier layer disposed in contact with an upper surface of the first portion, the electron barrier layer having a band gap energy larger than that of the first portion, and containing a p-type impurity; a second portion disposed in contact with an upper surface of the electron barrier layer and having one or more p-type semiconductor layers containing p-type impurities; The thickness of the second portion is smaller than the thickness of the first portion, A semiconductor laser device, wherein a lower end of the ridge is located in the first portion.

2. The semiconductor laser device according to claim 1 , wherein the first portion has a thickness of 400 nm or more.

3. 3. The semiconductor laser device according to claim 1, wherein the first portion has a thickness of 660 nm or less.

4. The semiconductor laser device according to claim 1 , wherein the second portion has a thickness of 260 nm or less.

5. The semiconductor laser device according to claim 1 , wherein the second portion has a thickness of 10 nm or more.

6. the second portion has an upper p-type semiconductor layer and a lower p-type semiconductor layer; the upper p-type semiconductor layer constitutes an upper surface of the ridge, 6. The semiconductor laser device according to claim 1, wherein the lower p-type semiconductor layer is disposed between the upper p-type semiconductor layer and the electron barrier layer and has a band gap energy larger than that of the upper p-type semiconductor layer.

7. the upper p-type semiconductor layer is made of GaN; 7. The semiconductor laser device according to claim 6, wherein the lower p-type semiconductor layer is made of AlGaN.

8. 8. The semiconductor laser device according to claim 6, wherein an Al composition ratio of said lower p-type semiconductor layer is smaller than an Al composition ratio of said electron barrier layer.

9. 9. The semiconductor laser device according to claim 1, wherein the shortest distance from the bottom surface of the ridge to the electron barrier layer is greater than the shortest distance from the top surface of the ridge to the electron barrier layer.

10. a p-electrode provided on an upper surface of the ridge; 10. The semiconductor laser device according to claim 1, wherein the p-electrode is a transparent conductive film having a refractive index smaller than that of the second portion.

11. 11. The semiconductor laser element according to claim 1, wherein the semiconductor laser element is capable of oscillating laser light having a wavelength of 530 nm or more.

12. the first portion has a top layer in contact with a lower surface of the electron barrier layer; the second portion has a bottom layer in contact with an upper surface of the electron barrier layer; 12. The semiconductor laser device according to claim 1, wherein the band gap energy of the lowermost layer is smaller than the band gap energy of the uppermost layer.

13. forming an n-side semiconductor layer on a substrate; forming an active layer on the n-side semiconductor layer; forming an undoped first portion having one or more semiconductor layers on an upper surface of the active layer; forming an electron barrier layer on a top surface of the first portion by doping with a p-type impurity, the electron barrier layer having a band gap energy larger than a band gap energy of the first portion; forming a second portion having one or more p-type semiconductor layers formed by doping a p-type impurity on an upper surface of the electron barrier layer; forming an upwardly protruding ridge by removing a portion of the p-side semiconductor layer including the first portion, the electron barrier layer, and the second portion; In the step of forming the second portion, the second portion is formed to have a thickness smaller than a thickness of the first portion; A method for manufacturing a semiconductor laser element, wherein in the step of forming the ridge, a part of the p-side semiconductor layer is removed so that a lower end of the ridge is located at the first portion.

Citation Information

Patent Citations

  • Semiconductor element

    JP2003273473A

  • Semiconductor laser, method of manufacturing semiconductor laser, optical pickup, and optical disk device

    JP2008124110A

  • Nitride semiconductor laser element

    JP2009141340A

  • Semiconductor light-emitting element

    JP2009239083A

  • Nitride semiconductor laser element

    JP2014131019A